The investigation of the mechanical properties of structural lightweight concrete produced with pumice and mineral admixtures - Yazicio?lu, Salih; Bozkurt, Nusret (My University, 2006)
This paper reports an experimental investigation carried out to evaluate the mechanical properties of structural lightweight concrete produced with pumice and mineral admixtures. CEM I 42,5 N cement used in the study was partially replaced with silica fume (SD) 10% and fly ash (UK) 30% by weight, respectively. The tests of compressive strength, split tensile strength and ultrasonic pulse velocity were performed in the specimens prepared with mineral admixtures at ages of 3, 7, 14, 28 and 90 days. From the results it was seen that specimens prepared with silica fume showed better strength properties than other test specimens. While control concrete specimens showed similar strength properties to concrete specimens with silica fume admixture at early ages those of concrete specimens with fly ash admixture did not increase at early ages. Furthermore, UK concrete series gave very close results to control concrete at advanced ages (90 days).
Pomza ve mi?neral katkili taşiyici hafi?f betonun mekani?k özelli?kleri?ni?n araştirilmasi
Keywords: Fly ash; Pumice; Silica fume; Structural lightweight concrete